Development of inertial and novel marker-based techniques and analysis for upper arm rotational velocity measurements in tennis - Ahmadi, A.; Rowlands, D. D.; James, D. A. (Sports Engineering, 2010)
This paper examines three methods to measure the upper arm rotation, the main contributor to produce a fast first serve in tennis. Accepted videography techniques were compared with a novel inertial gyroscope system and marker-based technique. A network of two inertial sensors on the upper arm and the chest was used to measure upper arm rotation angle and remove body artifacts. A marker-based virtual gyroscope (MBVG) was derived from Vicon marker positions in the standard Plug-in-Gait model using a vector-based method of marker trajectories and a series of geometric transformations. The results indicate that there is a close temporal feature match for all three methods when applied to the tennis serve. This paper shows that gyroscopes as well as the MBVG can be advantageous for tennis serve assessment.